(untitled) (Revista Contexto & Saúde, 2026)
Major depressive disorder is a reality to an increasing number of individuals worldwide, yet, it is still poorly understood and its treatment remains lackluster. Due to the subpar success rates of traditional monoaminergic pharmacotherapy, new targets have been explored. Here, the behavioral effects of a single dose of moxidectin (MOX) (1,5 mg/kg, 0,1 mL/10g, s.c.), a drug capable of allosterically modulating GABAA channels, was evaluated in male Swiss mice by the tail suspension (TST), splash (SPT), open field and elevated plus maze tests between 24 and 48 h post injection. MOX was capable of significantly decreasing the immobility time in TST and increasing grooming time in SPT, suggesting an antidepressant effect. To further explain the molecular pathways underlying MOX’s observed behavioral changes, neurotrophic factors and oxidative stress biomarkers were identified. An increase in brain-derived neurotrophic factor (Bdnf) mRNA was observed, possibly explaining the behavioral changes. An increase in total antioxidant capacity and glutathione S-transferase (GST) in the prefrontal cortex and a decrease of GST in the hippocampus of MOX-treated animals may have also contributed to these results. To our knowledge, this is the first study demonstrating the antidepressant-like effect of MOX in mice. While these results are preliminary, they’re promising. The utilization of GABAA modulators is an emerging and interesting new avenue to be explored in the treatment of neuropsychiatric ailments.